2002
DOI: 10.1046/j.1464-5491.2002.00784.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of diabetic retinopathy and screening procedures among diabetic people

Abstract: Patients' health perceptions and internal control mechanisms may be insufficiently developed for optimal participation in retinopathy screening. Diabetes care by long-term group education may address this problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 15 publications
2
24
1
4
Order By: Relevance
“…A lack of this knowledge was mentioned as a barrier among the unscreened group. Other studies have indicated that knowledge of eye disease appears to positively influence utilization of eye care services [24,25]. In our study an increased knowledge base of diabetic retinopathy other than recommended yearly exam did not significantly affect screening uptake.…”
Section: Discussioncontrasting
confidence: 71%
“…A lack of this knowledge was mentioned as a barrier among the unscreened group. Other studies have indicated that knowledge of eye disease appears to positively influence utilization of eye care services [24,25]. In our study an increased knowledge base of diabetic retinopathy other than recommended yearly exam did not significantly affect screening uptake.…”
Section: Discussioncontrasting
confidence: 71%
“…Educational methodologies should start with structured studies of patients and their beliefs and attitudes. A survey run jointly in DR screening clinics of Turin and South Wales suggests that many patients are not aware that diabetes can damage their eyes, that something can be done to prevent the damage and that they could actually help in the process [77]. An important portion of patients did not even realize they were being screened for diabetic eye disease, let alone why.…”
Section: Screening In the Patients' Perspectivementioning
confidence: 99%
“…More recent data suggest that implementing this management model could even prevent deterioration of retinopathy [79]. Having a specific knowledge of the retina or DR did not appear to influence awareness of the threat to eyesight or attitudes to prevention, suggesting that patient education should focus more on correct health conducts than on technicalities of diabetes complications [77].…”
Section: Screening In the Patients' Perspectivementioning
confidence: 99%
“…[4] To prepare effective method of health promotion about diabetes, baseline information about knowledge, attitude and practice regarding eye complication and eye care of diabetics is crucial. Such studies were conducted in India,[5] Australia[6] and Italy,[7] however to the best of our knowledge; no such study has been undertaken in the Middle East.…”
Section: Introductionmentioning
confidence: 99%